Interactional structural loads of the XV-15 rotor in airplane mode - Lim, J.W.; Tran, S. (My University, 2019)
An investigation of the rotor/airframe interactions of the XV-15 tiltrotor aircraft in airplane mode is conducted using high fidelity CFD. To separate the rotor installation effects, an isolated rotor and a half-span full aircraft are simulated at the cruise speeds of 160 and 220 knots. The installed rotor displays a doublet aerodynamic loading near the 270o azimuth along with low-frequency mode harmonic airloads in the first half of the cycle. The doublet aerodynamic loading is due to the interactions with the wing and the low-frequency harmonic airloads are due to the rotor dynamics and longitudinal cyclic pitch control. The installed rotor thrust and power display significant 3/rev loading that is typical for a three-bladed rotor. More importantly, the resulting low-frequency mode harmonic airloads trigger vibrations on the rotor as a forcing function. The installed rotor displays significant installation effects on the 2 to 4/rev harmonics of the blade torsional, flap, and lead-lag moments at 220 knots.